2018
DOI: 10.1097/ccm.0000000000002830
|View full text |Cite
|
Sign up to set email alerts
|

Renal Decapsulation Prevents Intrinsic Renal Compartment Syndrome in Ischemia-Reperfusion–Induced Acute Kidney Injury: A Physiologic Approach*

Abstract: Our results strongly suggest that renal decapsulation prevents the onset of an intrinsic renal compartment syndrome after ischemic acute kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Two beneficial effects of decapsulation have been previously described. One is the suppression of RIHP 26 , 27 , and the other is the improvement of renal tissue hypoxia 28 . Our results indicated that tubulointerstitial injury was dependent on RIHP.…”
Section: Discussionmentioning
confidence: 99%
“…Two beneficial effects of decapsulation have been previously described. One is the suppression of RIHP 26 , 27 , and the other is the improvement of renal tissue hypoxia 28 . Our results indicated that tubulointerstitial injury was dependent on RIHP.…”
Section: Discussionmentioning
confidence: 99%
“…As in other forms of ARDS, use of high positive end-expiratory pressure and/or tidal volumes increases intrathoracic pressure, right atrial pressure and right ventricular afterload, and can decrease cardiac output 140 . Right-sided heart dysfunction and increased venous pressures can result in increased interstitial and tubular hydrostatic pressure within the encapsulated kidney, which decreases net GFR and oxygen delivery to the kidney 146 . The observed association between mechanical ventilation or use of vasopressors with the risk of AKI further suggests that haemodynamic factors contribute to COVID-19 AKI 5 , 147 , 148 .…”
Section: Pathophysiology Of Covid-19 Akimentioning
confidence: 99%
“…This method can be applied to models of kidney diseases such as ischemia/reperfusion injury and polycystic kidney disease [18,19]. It also has disadvantages: it is limited to extracellular regions, it is difficult to use in clinical applications because of its invasiveness, and the oxygen tension and renal flow results might be affected by renal decapsulation [20]. Therefore, other hypoxia detection methods are currently under development: blood oxygen level–dependent magnetic resonance imaging (BOLD-MRI), nitroimidazole probes, and phosphorescence lifetime measurement [17].…”
Section: Measurement Of Oxygen Status In the Kidneymentioning
confidence: 99%